THE SKILL OF FORMING THE ENDURANCE OF YOUNG FOOTBALL PLAYERS TO COMPLEX SITUATIONS OF COMPETITION ACTIVITIES AND THE MOTIVE OF SUCCESS - Khaitov, A.U. (SCIENCE and SOCIETY, 2026)
This article examines the importance of motivation in the process of volitional training of teenage football players. It has been determined that athletes need to develop willpower to maintain stable motivation. It has been proven that in order to achieve high results in the careers of teenage football players, it is necessary, along with the desire, to develop motivation for success and patriotism.
Keywords: teenager; football; competition; difficult situation; will; determination; perseverance; pursuit of a goal; tolerance; motive; achievement; patriotism